Osteotomy for Laminoplasty without Soft Tissue Penetration, Performed Using a Harmonic Bone Scalpel: Instrumentation and Technique - Nickele, Christopher; Hanna, Amgad; Baskaya, Mustafa K. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background Laminoplasty in the case of intramedullary spinal tumor requires care to avoid neurologic injury. The harmonic bone scalpel provides a method of laminoplasty that can be done safely and quickly for this and other indications.Patients Five cases are presented, each of which required operative intervention, namely laminoplasty. The pathologies presented are one cervical intramedullary tumor, one thoracic intramedullary spinal mass, one lumbar extramedullary intradural tumor, and two cases of multiple lower brachial plexus nerve root avulsions requiring dorsal root entry zone (DREZ) lesion.Results These five patients underwent laminoplasty for either tumor resection or DREZ lesion. The laminotomies were performed using the BoneScalpel™ (Misonix Inc., Farmingdale, NY, USA), which is a harmonic bone scalpel instrument. This obviated the need to place any instrument under the intact lamina. Kerrison punches and various instruments were still used, but for purposes other than the bony removal of the laminoplasty.Conclusion These cases demonstrate that the BoneScalpel™ can be used to facilitate the laminar cuts while still allowing a safe and effective operation, even in cases as delicate as an intramedullary thoracic spinal cord tumor. The mechanism of action of the harmonic bone scalpel allows osteotomies without cutting or penetrating soft tissue and also leaves minimal bony defect.
Keywords: laminoplasty; bone scalpel; cervical spine; lumbar spine; thoracic spine